PENGARUH STRATEGI PEMBELAJARAN INKUIRI DAN KEMAMPUAN BERPIKIR KRITIS TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM DI SMA NEGERI 1 PANCURBATU - Meidi Harianto (Hijri, 2017)
The purpose of this study are: (1) to find out the learning result of Islamic religious education students who are taught by Inquiry strategy is higher than the result of learning of Islamic religious education which is taught by conventional learning; (2) to find out the learning result of Islamic religious education of students who have high critical thinking ability higher than those with low critical thinking ability, and (3) to know the interaction between learning strategy and critical thinking ability toward the learning result of Islamic education.This research is a quasi experimental type 2x2. In this design each independent variable and attribute variables are clarified into 2 ie Inquiry learning strategy (A1) and Conventional learning (A2) as well as high critical thinking ability (B1) and low critical thinking (B2). Where Inkuiri class as experiment class consists of 31 students with 18 female students and 13 other male students. Meanwhile in the control class were taught by Conventional learning with 39 students with 21 female students and 18 male students.Data collection techniques in the form of student observation and test result data. The findings of this study show that students who are learning with Inquiry learning strategy can be optimal for students who have high critical and critical critical thinking ability. Thus, Inquiry learning strategy and critical thinking ability give different influence to the result of learning of Islamic religious education in X-1 MIA / IIS and X-3 MIA / IIS class in SMA Negeri 1 Pancurbatu lesson year 2016/2017.